Lower leg anterior and lateral intracompartmental pressure changes before and after classic versus skate nordic rollerskiing - Woods, K. M.; Petron, D. J.; Shultz, B. B.; Hicks-Little, C. A. (Journal of Athletic Training, 2015)
Context: Chronic exertional compartment syndrome (CECS) is a debilitating condition resulting in loss of function and a decrease in athletic performance. Cases of CECS are increasing among Nordic skiers; therefore, analysis of intracompartmental pressures (ICPs) before and after Nordic skiing is warranted.